2016
DOI: 10.3389/fmars.2016.00067
|View full text |Cite
|
Sign up to set email alerts
|

Defatted Biomass of the Microalga, Desmodesmus sp., Can Replace Fishmeal in the Feeds for Atlantic salmon

Abstract: Microalgal biomass is a potential feed ingredient that can replace fishmeal and ensure sustainability standards in aquaculture. To understand the efficacy of the defatted biomass from the marine microalga, Desmodesmus sp. a 70-day feeding study was performed with Atlantic salmon (Salmo salar) smolts. Three groups of fish (av. wt. 167 g) were offered either a control feed (without the microalga) or the microalga-containing (10/20%) feeds. At the end of the feeding period, the growth indices (condition factor, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 43 publications
10
55
3
Order By: Relevance
“…On the contrary, such an increase was not detected in the fish fed on 20% alga-containing feeds. In our earlier study on Desmodesmus , a similar trend in SOD activities was noted [22]. Furthermore, the mRNA level of sod was apparently higher in the 10% alga-fed group compared to the level in the 20% alga-fed group.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…On the contrary, such an increase was not detected in the fish fed on 20% alga-containing feeds. In our earlier study on Desmodesmus , a similar trend in SOD activities was noted [22]. Furthermore, the mRNA level of sod was apparently higher in the 10% alga-fed group compared to the level in the 20% alga-fed group.…”
Section: Discussionsupporting
confidence: 80%
“…The SGR values obtained in the present study were slightly lower than those reported earlier [22, 26]. The TGC values in the present experiment were higher than those obtained by Sørensen et al [15], but were in the same range as reported by Hatlen et al [26].…”
Section: Discussioncontrasting
confidence: 67%
“…In order to satisfy this demand, the utilization of microalgae as an alternative to fishmeal is being widely studied in different fish species (Olvera-Novoa et al, 1998;Patterson and Gatlin, 2013;Kiron et al, 2016;Sørensen et al, 2016). Most microalgae are rich in fiber, mineral salts, trace-elements, vitamins, polyunsaturated fatty acids, chlorophylls and essential amino acids (EAA), fulfilling requirements of most commercial fish feed and avoiding supplementation of vitamins and amino acids (Vizcaíno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the recent increasing cost of fishmeal, researchers have started evaluating the economic feasibility and optimum usage of these novel proteins as fishmeal substitutes. Partial fishmeal replacement with algae is also possible (Kiron et al, 2012;Al-Asgah et al, 2016;Abdel-Warith et al, 2016;Radhakrishnan et al, 2016;Kiron et al, 2016;Kissinger et al, 2016), especially in tropical areas where they are found in plentiful amounts. Kiron et al (2016) observed that partial substitution of fishmeal with defatted biomassof Desmodesmus sp.…”
Section: Novel Proteinsmentioning
confidence: 99%
“…Partial fishmeal replacement with algae is also possible (Kiron et al, 2012;Al-Asgah et al, 2016;Abdel-Warith et al, 2016;Radhakrishnan et al, 2016;Kiron et al, 2016;Kissinger et al, 2016), especially in tropical areas where they are found in plentiful amounts. Kiron et al (2016) observed that partial substitution of fishmeal with defatted biomassof Desmodesmus sp. in the feed of Atlantic Salmon does not have any adverse effects on the specific growth rate, condition factor, protein efficiency ratio and whole body proximate composition of fish.…”
Section: Novel Proteinsmentioning
confidence: 99%